See The Potential of Dividend Policy and Profitability in Increasing Company Value - Mutmainah Mutmainah; Akhmadi Akhmadi (Indonesian Journal of Innovation Multidisipliner Research, 2024)
The purpose of this study is to assess how dividend policy affects the way that profitability and firm value are related. The study focuses on companies in the oil and gas subsector that are listed between 2018 and 2023 on the Indonesia Stock Exchange. Seven companies were selected as a sample using purposive sampling. Descriptive statistics, Moderated Regression Analysis (MRA), and hypothesis testing are used in the analysis. The results imply that company value is not much impacted by profitability alone. On the other hand, when dividends are paid out, the dividend policy serves as a direct moderator, strengthening the positive relationship between profitability and company value. This is in line with the signaling hypothesis, which holds that dividend payments tell investors about the company's financial health and prospects for the future. However, the findings are not broadly applicable as the study is confined to the oil and gas subsector and uses only one proxy for each variable. Future research should broaden the scope to multiple subsectors and incorporate several proxies for each variable.